Self-identification of local civilizations under the conditions of globalization processes - Кошетар, У. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2017)
The article deals with the problems of self-identification of local civilizations in the context of globalization accompanied by migration and the clash of cultures. The author give grounds that the policy of multiculturalism should be aimed at preventing of international and inter-ethnic conflicts.